The influence of cognitive styles as promoters of entrepreneurial orientation and intrapreneurship as drivers of innovation: The case of nurses in health services in Portugal in times of COVID-19 - Paula Ferraz; Carla Susana Marques; Gina Marques Carvalho Santos; Ariana Moreno Cunha; Sérgio Vaz (Administrative Sciences, 2021)
The main objective of this study is to assess how cognitive styles promote individual entrepreneurial orientation (IOE) and intrapreneurship and how they drive innovation among nurses in the healthcare services in Portugal. A total of 667 nurses participated, by completing an online questionnaire in the midst of the COVID-19 pandemic, working in different health units in Portugal. PLS-SEM structural equation modelling was used as a data analysis technique. The results show that cognitive styles have a positive influence on nurses' IOE; that cognitive styles have a positive influence on intrapreneurship, which is mediated by the IO; that the IOE impacts nurses' intrapreneurship and innovation, which is mediated by intrapreneurship; and that intrapreneurship impacts nurses' innovation. The originality of this study lies in the absence of studies showing relationships between the dimensions that we propose to analyze during the pandemic of COVID-19.
Keywords: 350; cognitive styles; COVID-19; individual entrepreneurial orientation; innovation; intrapreneurship; nurses